Solidarity and Discrimination Within and Between Generations: Evidence from a Dutch Population Sample - Arno Riedl; Hans Schmeets; Peter Werner (Institute of Labor Economics (IZA), 2025)
Using an artefactual field experiment, we elicit revealed preferences for solidarity of different age groups toward the same and other age groups among a large, diverse Dutch population sample. Preferences are measured with a solidarity game and linked to a unique administrative database, allowing exploration of demographic and socio-economic correlates. In the game, a winner of a money amount is asked ex-ante how much they are willing to transfer to a loser who gets nothing. Participants, on average, show a strong preference for ex-ante solidarity, willing to transfer about 40% of the money. However, participants are overly pessimistic about what others will transfer. We also observe age-based discrimination, as many show stronger solidarity with their own age group. Using questionnaires, we measure stated preferences in various domains and find revealed preferences correlate with some self-reported attitudes and with opinions on social security and solidarity-related field behavior.
Keywords: D63; D64; D91; C93; 330; social security systems; group identity; age groups; solidarity; large population sample